De las exigencias genéricas a la emergencia del texto literario: el problema de los géneros - Forero Olaya, Nicolás Camilo (Enunciación, 2016)
This article presents a theoretical and methodological model, based on Discourse Studies, which allows to eliminate tensions that has beengenerated between the study of the so-called "natural" genres and the study of the so-called “historical” genres in Literary Genre’s Theory.To this end, the tension is examined as well as different perspectives used for the constitution of the model (Socio-communicative perspective from Patrick Charadeau (2012), and the perspective based on social practices from Isolda Carranza (2012)), from which theconcepts of situation of communication, demands and contextualize contribute to such effect. It is conclude that the demands that each genre formula sets for the author, determine both the elements that the natural genre are chosen for the realization of the literary text and the contributions that the author makes, in accordance with a social environment and literary environment. <!--[endif]-->